2019
DOI: 10.1038/s41598-019-39913-9
|View full text |Cite
|
Sign up to set email alerts
|

Independent and combined effects of diethylhexyl phthalate and polychlorinated biphenyl 153 on sperm quality in the human and dog

Abstract: A temporal decline in human and dog sperm quality is thought to reflect a common environmental aetiology. This may reflect direct effects of seminal chemicals on sperm function and quality. Here we report the effects of diethylhexyl phthalate (DEHP) and polychlorinated biphenyl 153 (PCB153) on DNA fragmentation and motility in human and dog sperm. Human and dog semen was collected from registered donors (n = 9) and from stud dogs (n = 11) and incubated with PCB153 and DEHP, independently and combined, at 0x, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 51 publications
0
40
0
1
Order By: Relevance
“…This result is in line with the findings of our previous study that examined the impact of prenatal exposure to DEHP on the F1 male fertility in mice 33 . The lower fertility in the paternal line may be caused by a problem in sperm motility or sperm DNA fragmentation as a recent study showed that DEHP exposure leads to reduced sperm motility and increased sperm DNA fragmentation 69 . Another possibility is decreased sperm capacitation, a process that is regulated by the cholesterol contents in the sperm membrane 70 .…”
Section: Discussionmentioning
confidence: 99%
“…This result is in line with the findings of our previous study that examined the impact of prenatal exposure to DEHP on the F1 male fertility in mice 33 . The lower fertility in the paternal line may be caused by a problem in sperm motility or sperm DNA fragmentation as a recent study showed that DEHP exposure leads to reduced sperm motility and increased sperm DNA fragmentation 69 . Another possibility is decreased sperm capacitation, a process that is regulated by the cholesterol contents in the sperm membrane 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to EDCs poses a significant risk to reproductive health and fetal development (Brehm et al 2018;Hannon, Niermann, and Flaws 2016). While it is known that DEHP impairs sperm motility and chromatin DNA stability (Sumner et al 2019;Pant et al 2011), its mechanism of action and direct effect on sperm fertilizing capacity have not been elucidated. In this study, we aimed to determine the acute effect of DEHP on sperm fertility.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of combined exposure to multiple chemicals are not the superimposed effects of each. There are possibly synergistic or antagonistic actions among them (48,49).…”
Section: Discussionmentioning
confidence: 99%